2014
DOI: 10.9734/bjmmr/2014/9480
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Quiz Competition: A Innovative Method of Teaching and Learning in Undergraduate First Year Medical Course at RAKMHSU, UAE

Abstract: Objectives:The main objective of this innovative active learning approach was to increase student's interest in basic science subjects and to enhance student participation in acquiring the knowledge in the core and applied aspects of anatomy, physiology and biochemistry. Study Design: Comparative cross sectional study. Place and Duration of Study: Ras Al Khaimah medical and health Sciences University, 6monthsMethodology: It was a comparative cross sectional study to find out whether Quiz competitions are effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…They fell that the positive experience during learning enhanced team effort and communication in addition to enhancing recall of factual knowledge. 15 Also in their study, Vasan et al showed that student performance improved and students perceived it as motivational collective team learning that was self directed and fostered pear respect. 16 The development of innovative methods is important toimprove student performance.…”
Section: Discussionmentioning
confidence: 96%
“…They fell that the positive experience during learning enhanced team effort and communication in addition to enhancing recall of factual knowledge. 15 Also in their study, Vasan et al showed that student performance improved and students perceived it as motivational collective team learning that was self directed and fostered pear respect. 16 The development of innovative methods is important toimprove student performance.…”
Section: Discussionmentioning
confidence: 96%